2019
DOI: 10.3390/antibiotics9010011
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Local Pharmacotherapeutics and Adjunctive Agents for Nonsurgical Treatment of Periodontitis: A Contemporary Review of Clinical Efficacies and Challenges

Abstract: Periodontal infections tend to be site-specific, mostly confined to the periodontal pocket. With the surge of antibiotic-resistant bacteria, the trend is shifting towards other therapeutic modalities, especially locally delivered approaches that include other pharmacotherapeutic drugs and medical devices. This narrative review aimed to provide insights into the clinical efficacy of local drug delivery and adjunctive agents used in nonsurgical management of periodontitis. Electronic (PubMed/MEDLINE, CENTRAL, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 163 publications
(178 reference statements)
0
29
0
Order By: Relevance
“…A weighted mean difference (WMD) of 0.56 mm in PPD reduction and 0.53 mm CAL gain was seen in a review on the use of xanthan-based chlorhexidine gel (Chlosite®) as an adjunctive agent for nonsurgical treatment of periodontitis. [ 22 ] A recent systematic review by Zhao et al concluded that adjunctive placement of xanthan-based chlorhexidine gel (Chlosite®) at individual sites provided slight benefit in PPD reduction when compared with nonsurgical periodontal therapy (NSPT) alone. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…A weighted mean difference (WMD) of 0.56 mm in PPD reduction and 0.53 mm CAL gain was seen in a review on the use of xanthan-based chlorhexidine gel (Chlosite®) as an adjunctive agent for nonsurgical treatment of periodontitis. [ 22 ] A recent systematic review by Zhao et al concluded that adjunctive placement of xanthan-based chlorhexidine gel (Chlosite®) at individual sites provided slight benefit in PPD reduction when compared with nonsurgical periodontal therapy (NSPT) alone. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the locally used antibiotic, and antiseptic intra-pocket drug delivery system ensure a higher concentration of active content in the gingival crevice fluid therefore advanced effectiveness, and better patient compliance could be achieved 35 . Different locally used drug delivery systems are developed from the strips, fibers, or microparticles, but next to the opportunities stay deficiencies into the individual types [36][37][38] . The local administrations provide benefits as the less drug needed but the usage of the appropriate dose is often a challenge in a real situation 39 .…”
Section: Study Of Drug Release Properties On Different Phmentioning
confidence: 99%
“…Additionally, in the last decades, a number of novel strategies encompassing the use of locally delivered antiseptic and/or antiinflammatory agents, antibiotics or photodynamic therapy, have been tested to enable a more accurate disruption and removal of the subgingival biofilm and to additionally improve the clinical outcomes and reduce the need for surgery [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%